Performance of membrane bioreactor system with sludge ozonation process for minimization of excess sludge production - Song, KG; Choung, YK; Ahn, KH; Cho, JW; Yun, HJ (ELSEVIER SCIENCE BV, 2003)
This study investigated the effects of sludge ozonation on excess sludge minimization and enhancement of nutrient removal in membrane bioreactor (MBR). Two modified Ludzack-Ettinger (MLE) type MBR system were operated in parallel with or without a batch-type sludge ozonation process. A flat type microfiltration membrane (pore size 0.4 mum) was used. The specific ozone dosage was set at 0.1 gO(3)/gSS. In the control run (without sludge ozonation), the daily sludge production was about 1.04 g/d. However, in the ozone run (with sludge ozonation), the daily sludge production was negligible. In addition, the MLSS concentrations and the volatile fraction of MLSS in the reactor maintained constant around 8,000 mg/L and 0.75, respectively, without excess sludge. The concentration of effluent was maintained at a satisfactory level in both runs. Furthermore, the MBR system with sludge ozonation process showed relatively better nutrient removal than without sludge ozonation. It revealed that ozonated sludge might be completely degraded in the reactor and effectively used as a carbon source. During the operation, the transmembrane pressure was maintained lower than 10 kPa under 0.36 m/d of flux regardless of presence of sludge ozonation. Application of sludge ozonation to the MBR system was significantly effective for minimization of excess sludge production as well as for enhancement of nutrient removal.